2012
DOI: 10.1073/pnas.1119881109
|View full text |Cite
|
Sign up to set email alerts
|

Ligands and signaling proteins govern the conformational landscape explored by a G protein-coupled receptor

Abstract: The dynamic character of G protein-coupled receptors is essential to their function. However, the details of how ligands stabilize a particular conformation to selectively activate a signaling pathway and how signaling proteins affect this conformational repertoire remain unclear. Using a prototypical peptide-activated class A G protein-coupled receptor (GPCR), the ghrelin receptor, reconstituted as a monomer into lipid discs and labeled with a fluorescent conformational reporter, we demonstrate that ligand ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
99
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(115 citation statements)
references
References 27 publications
(23 reference statements)
14
99
0
2
Order By: Relevance
“…In agreement with our previous study (Canals et al, 2012), BQCA exhibited key hallmarks of allostery within a two-state system at the WT M 1 mAChR, including positive or negative modulation of orthosteric ligand activity depending on the nature of the orthosteric ligand (i.e., positive or inverse agonist) and different strengths of cooperativity depending on the intrinsic efficacy of the orthosteric ligand and the magnitude of stimulus-response coupling of the studied signal pathway. It can, of course, be questioned as to how an allosteric modulator can behave in a manner consistent with a two-state model at GPCRs given that these receptors adopt a larger spectrum of biologically active states, a prerequisite, in fact, for biased signaling (Vaidehi and Kenakin, 2010;Mary et al, 2012). This can be reconciled within a model whereby the modulator changes the abundance, but not the quality/nature, of different microstates that govern receptor activity; an overall change in abundance of active microstates in one direction relative to "inactive" microstates would still appear, at a macroscopic level, as a "two-state" system.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our previous study (Canals et al, 2012), BQCA exhibited key hallmarks of allostery within a two-state system at the WT M 1 mAChR, including positive or negative modulation of orthosteric ligand activity depending on the nature of the orthosteric ligand (i.e., positive or inverse agonist) and different strengths of cooperativity depending on the intrinsic efficacy of the orthosteric ligand and the magnitude of stimulus-response coupling of the studied signal pathway. It can, of course, be questioned as to how an allosteric modulator can behave in a manner consistent with a two-state model at GPCRs given that these receptors adopt a larger spectrum of biologically active states, a prerequisite, in fact, for biased signaling (Vaidehi and Kenakin, 2010;Mary et al, 2012). This can be reconciled within a model whereby the modulator changes the abundance, but not the quality/nature, of different microstates that govern receptor activity; an overall change in abundance of active microstates in one direction relative to "inactive" microstates would still appear, at a macroscopic level, as a "two-state" system.…”
Section: Discussionmentioning
confidence: 99%
“…Early work by Gurevich et al (1997) found that a b-arrestin bound receptor showed a markedly higher affinity for agonists than the nonoccupied receptor, which is in accordance with the expectations of a ternary complex model. A more recent study using double-exponential fluorescent lifetime decay analysis showed distinct ghrelin receptor conformational changes upon addition of b-arrestin (or G q protein) in reconstituted lipid nanodiscs (Mary et al, 2012). The receptor activity modifying proteins (RAMPs) are another striking example of a single-transmembrane-spanning protein family that can associate with certain GPCRs (predominantly class B receptors) to create new receptor phenotypes or to bias signaling (McLatchie et al, 1998;Christopoulos et al, 1999Christopoulos et al, , 2003Hay et al, 2006).…”
Section: Endogenous Allosteric Modulatorsmentioning
confidence: 99%
“…Different cobinding ligands have been shown to affect the receptor affinity of ligands in accordance with this allosteric reciprocity (i.e., salvanorin affinity for k-opioid receptors with Ga 16 versus Ga i2 ; Yan et al, 2008 and changes in ghrelin receptors with addition of b-arrestin to nanodiscs, Mary et al, 2012). In view of the fact that functional response depends on the ternary complex of agonist/receptor/signaling protein (Onaran and Costa, 2012), it is conceivable that the affinity of the receptor-signaling complex shows variable affinity for agonists depending on the nature of the signaling protein interacting with the receptor.…”
Section: Quantifying Biasmentioning
confidence: 99%